Reduce the application of phosphorus fertilizer in peanut fields and improve its efficiency by using iron modified biochar to adsorb phosphorus recovery products - Zhang, Junxiao; Bu, Xiangxi; Huang, Zhenyu; Wu, Changxue; Xie, Xiangwen (Frontiers in Plant Science, 2024)
Introduction To address the scarcity of agricultural phosphorus (P) fertilizers and reduce phosphorus accumulation in wastewater, this study employed iron-modified biochar (Fe-B) to adsorb phosphorus from water. The phosphorus-loaded iron-modified biochar (Fe-BP) was subsequently applied to peanut fields. Batch experiments were conducted to determine the optimal adsorption parameters and mechanism of Fe-B for phosphate ions (PO43−). Methods The field experiment utilized a randomized complete block design, comprising the following treatments: no biochar and no P fertilizer (B0P0), no biochar with conventional phosphate fertilizer (B0P1, CK, P2O5 at 144 kg ha−1), biochar with CK (B1P1), Fe-B with CK (FeB-P1), phosphorus-loaded Fe-B with CK (FeBP-P1), and phosphorus-loaded Fe-B with two-thirds CK (FeBP-P2, P2O5 at 96 kg ha-1). Results The results demonstrated that the biochar dosage of 0.05 g (2 g L-1) results in a phosphate removal rate exceeding 80%. Optimal adsorption efficiency occurs within a pH range of 6-9, with a sharp decline observed at pH values above 10. The presence of NO3-, Cl-, and SO42- does not significantly affect the phosphate adsorption capacity of Fe-B, unlike HCO3- and CO32-, which reduce it. After the fifth desorption and recycling process, the adsorption capacity of the biochar decreased to 24%. The peanut yield in the FeB-P1 treatment was 50.8% higher than that in the FeBP-P2 treatment. While the phosphorus recovery efficiency (REP) does not significantly differ between FeBP-P2 and B1P1 treatments, both are superior to B0P1. Moreover, FeBP-P2 facilitated the available phosphorus concentration in the root zone. Discussion Overall, phosphorus-loaded iron-modified biochar reduced the required amount of phosphorus fertilizer, maintain peanut yield, and enhanced phosphorus fertilizer utilization efficiency.